ANALISIS LINGKUNGAN KERJA PADA CREDIT UNION BINA MASYARAKAT (BIMA) KANTOR PUSAT SINTANG - Evy Ratnasari (Universitas Kapuas Sintang, 2025)
The physical work environment includes the availability of supporting facilities and infrastructure, factors such as color, lighting, safety, and noise levels that contribute to employees' comfort at work. A comfortable work environment directly impacts employee performance, especially in completing assigned tasks. One way to improve employee performance is by creating a work environment that is comfortable, safe, conducive, and pleasant.In addition, the non-physical work environment encompasses social interactions in the workplace, including formal and informal relationships between superiors and subordinates, as well as among employees. These good relationships aim to foster harmonious collaboration to achieve organizational goals. A harmonious work relationship has already been established at CU Bima Headquarters in Sintang. Based on the research findings, several recommendations are provided. First, CU Bima Headquarters in Sintang is encouraged to regulate the use of music in the workplace to create a comfortable work atmosphere. Second, supervisors are advised to pay more attention to building relationships with subordinates and improving communication between employees and leaders, ensuring that work-related information is conveyed clearly and accurately.